The effectiveness of the flipped learning strategy in the achievement of tenth-grade middle school students in Kurdish literature - Mohammed, Abdulsatar; Nabi, Molod (Humanities Journal of University of Zakho, 2023)
The current research aims to identify the effectiveness of the flipped learning strategy in the achievement of tenth-grade preparatory students in Kurdish literature. The researchers adopted the experimental design of equal groups with dimensional tests for the General Directorate of Education of Dohuk Governorate, and it consisted of (2702) male students and (2909) female students, in (23) preparatory and secondary schools for males, and (21) schools for females for the academic year (2021-2022) such as (Martyr Mulla Amin for Girls), and they chose the classes randomly. In (Bativa Preparatory School for Boys), Division (A) was chosen for the experimental group, the number of its members was (23) students, and Division (B) was for the control group, and the number of its members was (22) students. In the same way, groups were selected in (Martyr Mulla Amin Preparatory School for Girls), where (27) students were selected in Division (C), and (22) students in Division (A) for the control group. Kurdish literature was taught to the two experimental groups with a strategy of Reversed learning, while the two control groups were taught in the usual way. The two researchers prepared a test that included (35) items, which were divided into three questions, the first question (20) items of the multiple choice type, the second question (4) items of the type (true or false), and the third question (11) items of the type of essays with Specific answers, and extracted the psychometric characteristics of the test. After completing the experiment, which lasted a full semester, the researchers applied the tool and conducted statistical handling of the data using the (t.test) test for two independent samples of different numbers. The results showed the effectiveness of the flipped learning strategy in the achievement of the students of the two experimental groups compared to the two control groups.